Two new species of Pseudapis Kirby, 1900 (Hymenoptera: Halictidae: Nomiinae) from Africa - Bossert, Silas; Pauly, Alain (Zootaxa, 2019)
Two previously unknown species of the genus Pseudapis Kirby, 1900 are described and illustrated: Pseudapis neumayeri Bossert & Pauly, sp. nov. (♂, ♀, Kenya, Tanzania), and P. crassivertex Bossert & Pauly, sp. nov. (♂, ♀, Mali, Mauritania, Niger, Senegal). We provide diagnoses for the new species and report all currently available records. Lastly, we present a revised identification key for the African species of the genus.